Development of the synthesis technology of S@AgCl−Ag2S nanocomposite in aqua medium - Khan, N.V.; Burkitbayev, M.M.; Urakaev, F. Kh. (KSU publ., 2019)
This research work is devoted to the development of the synthesis technology of nanocomposite based on sulfur, silver chloride and silver sulfide. The components which included in this nanocomposite make it possible to use it in various fields of science and technology: from biomedicine to agriculture.S@AgCl−Ag2S nanocomposite was synthesized in aqua medium by two stages: 1) separate obtaining of each component; 2) mixing of all systems (products of reactions). The first stage is based on the interaction of aqueous solutions of silver nitrate with sodium chloride and sodium thiosulfate (in excess) with hydrochloric acid. Each of these reactions was carried out separately. At the second stage there was formation of silver sulfide and directly the S@AgCl−Ag2S nanocomposite, under interaction of all products of the first stage. The physicchemical characteristics of the samples were determined by X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy and energy dispersive X-ray spectroscopy (SEM-EDAX). The results of XRD and Raman spectroscopy of the samples showed that nanocomposite represented by silver chloride, silver sulfide and sulfur. EDAX analysis identified the presence of silver, chlorine and sulfur. Meanwhile SEM analysis revealed that investigated material has range of particles size from micro to nano ones. Morphology of particles mostly represented by oval and spherical forms, and smooth surface.
Keywords: nanocomposite; nanoparticles; sulfur; silver halides; silver chloride; silver sulfide; aqua medium; aqueous solution